Pathoprevalence of infectious diseases of goat emphasizing on endoparasitic lesions at Dinajpur Sadar - Akther, Mahfuza; Islam, Md Nazrul; Ali, Md Haydar; Rashid, SM Harun ur; Haque, Md Anowarul (Asian Journal of Medical and Biological Research, 2017)
This study was conducted to investigate the pathoprevalence of different infectious diseases of goat at Sadar upazilla of Dinajpur district in Bangladesh. Infectious cases were recorded with respect to breed, sex, age and season from Upazilla Veterinary Hospital and District Veterinary Hospital, Sadar, Dinajpur during July, 2014 to June, 2015 and diagnosis was made on the basis of clinical history, clinical examinations and common laboratory techniques with histopathological examination. A total of 2139 infectious diseases were founded and categorized by the causal agents where the highest prevalence was observed in mixed infectious diseases (46.06%) followed by viral diseases (28.93%), internal parasitic diseases (9.77%), external parasitic diseases (8.42%), bacterial diseases (3.00%), protozoal diseases (2.01%) and lowest was in fungal diseases (1.83%). The prevalence of infectious disease was significantly higher at Jamunapari (55.12%) than Black Bengal (44.88%). Female goats were more susceptible (54.32%) than male (45.68%). The prevalence was varied according to age and highest was in G-1 (45.48%) followed by G-2 (36.48%) and G-3 (17.68%). Summer season (33.60%) was common for infections followed by winter (33.51%) and rainy (32.89%). Most of the internal lesions were produced by the endoparasitic infections which were examined microscopically. These results indicate that, the prevalence of various infectious diseases in the goats was higher at Sadar, Dinajpur thus, there is a need for an appropriate control measures in order to prevent and minimize the loss caused by such diseases and this study may help to develop strategies against the infectious diseases of goat. Asian J. Med. Biol. Res. June 2017, 3(2): 254-266